BRICS Expansion and The Emergence of A New Economic World Order - Mukhtar Imam (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
The BRICS group, composed of Brazil, Russia, India, China, and South Africa, has emerged as a significant economic bloc challenging the traditional Western-dominated economic order. The expansion of BRICS aims to create a more multipolar world, offering alternative frameworks for global economic governance. This article explores the historical context, motivations, and implications of BRICS expansion and its potential to redefine the global economic landscape. The expansion of the BRICS (Brazil, Russia, India, China, and South Africa) group marks a pivotal moment in the global economic landscape, challenging the dominance of traditional Western-led institutions. This article explores the historical development of BRICS, its recent expansion to include new members and the implications of this growth for shifting economic world order. By analyzing the motivations behind BRICS' expansion, its collective economic potential, and its geopolitical strategies, this study highlights the emerging multipolar world and its potential to redefine global governance, trade, and finance. The article underscores the strategic intent of BRICS to champion equitable development, promote South-South cooperation, and challenge dollar hegemony, thereby signaling a profound transformation in international relations.